Impact of Delayed Artificial Aging on Tensile Properties and Microstructural Evolution of Directed Energy Deposited Scalmalloy® - Rachel Boillat-Newport; Sriram Praneeth Isanaka; Frank Liou (Applied Sciences)
Scalmalloy® is a novel alloy designed to work with the unique processing inherent in additive manufacturing (AM). This alloy is post-processed using a single artificial aging treatment rather than a multistep heat treatment, as often noted in traditional manufacturing processes. Much of the literature details the impact of direct aging treatments around the temperature and time recommended by the manufacturer, 325 °C for 4 h; however, few studies have explored the impact of delayed artificial aging on the resulting mechanical and microstructural behavior. This study explored this missing link and determined the impact that the time between the fabrication of the component and artificial aging has on the final properties. For this study, directed energy deposition (DED) was utilized to fabricate Scalmalloy® components. Post-processing via artificial aging was performed after fabrication to yield samples naturally aged for 0, 2, 4, 6, 8, 10, 12, and 14 days. Samples were subsequently aged at 325 °C for 4 h. Tensile testing determined that natural aging negatively impacts tensile strengths. After 6 days of delayed artificial aging (6 NA), the yield strength (YS) and tensile strength (TS) relative to day 0 (0 NA) case were diminished by 10% and 8.6%, respectively. After 12 days (12 NA), even greater property decreases were noted, with a 23% decrease in YS and an 18% decrease in TS. Microstructural characterization was performed and an increase in precipitate size and decrease in precipitate number coupled with increased grain sizes were theorized to be linked to the decrease in tensile properties. The negative impact of delayed artificial aging after AM fabrication for Scalmalloy® highlights the importance of fast transitions from deposition to heat treatment.